Green Campus initiative and its impacts on quality of life of stakeholders in Green and Non-Green Campus universities - Ronnachai Tiyarattanachai; Nicholas M. Hollmann (My University, 2016)
In 2010, Universitas Indonesia (UI) developed the UI GreenMetric World University Ranking for universities to share information about their sustainability practices. This ranking system was well aligned with the basis of Sustainability for Higher Education. The scoring system can also be used as a guideline for universities to achieve sustainability in their campuses. Since its first launch, more universities around the world have increasingly participated in the ranking system including many universities in Thailand. This study compared perception of stakeholders in Green Campus and Non-Green Campus universities in Thailand regarding stakeholders' satisfaction on sustainability practices and perceived quality of life at their campuses. The results showed that stakeholders at the studied Green Campus University were more satisfied and had significantly better perceived quality of life compared to stakeholders from the studied Non-Green Campus university. The results suggested that universities should adopt the criteria set in the UI GreenMetric World University Ranking to achieve better sustainability in their campuses and improve quality of life of their stakeholders.
Keywords: University campus; Sustainability in Higher Education